The Stalin era - Boobbyer, Philip (Routledge sources in history., 2000)
A wide ranging history of every aspect of Stalin's dictatorship over the peoples of the Soviet Union. It places the man and his ideology into context both within pre-Revolutionary Russia, Lenin's Soviet Union and post-Stalinist Russia.